ANALISIS PENGARUH PRODUK DOMESTIK BRUTO (PDB), INVETASI, TENAGA KERJA TERHADAP TINGKAT KEMISKINAN DI INDONESIA TAHUN 2001-2010 - Siti Sholihah; Lorentino Togar Laut; Gentur Jalunggono (DINAMIC : Directory Journal of Economic, 2019)
Poverty is a complex issue that is difficult to solve in almost every region in Indonesia. Poverty is socio-economic measurement in assessing the success of the government's development. There are so many negative social problems that are arising due to increasing poverty rate. This study aims to determine the effect of gross domestic product, invesment, labor (dependent variable) on poverty levels (independent variables) in Indonesia from 2001 to 2010 where poverty levels used data on the number of poor people. The method in this study is quantitative deskriptive using multiple linear analysis. The testing model was carried out with the version 24.0 SPSS software. The type of data obtained is secondary data from 2001 to 2010. Statistical testing in this study uses the classic assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Then continued by testing the coefficient of determination r2, t test and test f. The  results  of  the  study  show  that  simultaneously  the  variables  of  gross  domestik  product, invesment, labor have a significant effect on the level of proverty. Partially gross domestic product to the poverty level directly is very small but the relationship is negative and significant while invesment and labor do not significantly influence poverty.